Devil [videorecording (DVD)] - Dowdle, John Erick; Messina, Chris; Marshall-Green, Logan, 1976-; Arend, Geoffrey, 1978- (Universal Studios Home Entertainment, 2010)
Trapped in an elevator high above Philadelphia, five people discover that the Devil is among them, and no one can escape their fate. This chilling, supernatural thriller will keep you on the edge of your seat all the way to a heart-stopping ending with a truly wicked twist.